Sesquiterpene lactone, a potent drug molecule from artemisia pallens wall with anti-inflammatory activity - Ruikar, Anjali D.; Misar, Ashwini V.; Jadhav, Ravindra B.; Rojatkar, Supada R.; Mujumdar, Arvind M.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Arzneimittel-Forschung-Drug Research, 2011)
The present study was carried out to investigate the anti-inflammatory activities of bioactive secondary metabolites of Artemisia pallens Wall, an aromatic herb from family Asteraceae. The results provide evidence for the topical anti-inflammatory properties of Artemisia pallens Wall. The compounds were isolated from the acetone extract of the plant material. The isolates were tested on Swiss albino mice using 12-O-tetradecanoyl phorbol-13-acetate (TPA) induced ear edema. One of the molecules from the extract indicated potent anti-inflammatory activity equivalent to indometacin (CAS 53-86-1). Elucidation of the molecular structures by single crystal x-ray diffraction studies revealed the conformational differences that the six membered rings in both the molecules are at an angle of 28.79 degrees. Presence of hydroxy function for compound 2 may be responsible for higher potency.
Keywords: Anti-inflammatory activity; Artemisia pollens; Asteraceae; Mice; Single crystal x-ray structure

Two antibacterial spiro compounds from the roots of Artemisia pallens wall: evidence from molecular docking - Honmore, Varsha S.; Natu, Arun D.; Khedkar, Vijay M.; Arkile, Manisha A.; Sarkar, Dhiman; Rojatkar, Supada R. (Natural Product Research, 2022)
Bioassay-guided isolation from acetone extract of the roots of Artemisia pallens Wall yielded two spiro compounds (1 and 2). The structures of these compounds were determined on the basis of spectroscopic techniques such as IR, MS, 1 D and 2 D- NMR. The acetone extract, fractions and the isolated two compounds were investigated for their antibacterial activity against two gram negative (E. coli, P. aeruginosa) and two gram positive (S. aureus, B. subtilis) bacterial strains. Compound (2) showed the best spectra of activity with IC50 and MIC values between 2.48-3.08 and 12.78 - 21.77 mu M and Compound (1) with 2.57-3.69 and 38.17 - 80.57 mu M, respectively, for the four bacterial strains, whereas inactive against Mycobacterium tuberculosis. Molecular docking study could further help in understanding the various interactions between these compounds and DNA gyrase active site in detail and thereby could provide valuable insight into the mechanism of action.
Keywords: antibacterial activity; antimycobacterial activity; Artemisia pallens; Asteraceae; Molecular docking; spiro compound